Vaccines against Covid-19: the Comparative Estimates of Risks in Adenovirus Vectors - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика)
Relevance. The vaccine against the SARS-Cov-2 coronavirus is considered as the most promising approach to curb (tame) a current pandemic and prevent new one. Three vaccines (AstraZeneca’s СhAdOx1 nCov-19, CanSino’s vaccine and Russia’s Sputnik V one) are in Phase III clinical trials and have the S protein as immunogen but different adenovirus vectors. It is known adverse neurological events associated with the СhAdOx1 nCov-19 vacсine.Aim is to investigate the distribution of homologous sequences of adenovirus proteins in human nervous and immune systems proteins, estimate potential risks of using adenovirus vectors in vaccines and discuss possible mechanisms inducing immune damage in the nervous system.Materials and methods. For the computer analysis of peptide (immune epitope) relationship between adenovirus structural proteins and human proteins, the search of homologous sequences was made. All protein sequences were used from databases available on the INTERNET.Results. Among adenoviruses (НАд5, НАд26 , ChАдY25, and SAd3) ChАдY25 has the highest content of sequences homologous to human nervous system proteins that may be the cause of autoimmune complications in vaccination.Conclusion: In AstraZeneca’s СhAdOx1 nCov-19 vaccine there are a large number of peptide sequences homologous to human nervous system proteins and it allows to predict the possible risks with this vaccine.